2021
DOI: 10.3389/fcell.2021.620248
|View full text |Cite
|
Sign up to set email alerts
|

Investigating Molecular Determinants of Cancer Cell Resistance to Ionizing Radiation Through an Integrative Bioinformatics Approach

Abstract: Eradication of cancer cells through exposure to high doses of ionizing radiation (IR) is a widely used therapeutic strategy in the clinical setting. However, in many cases, cancer cells can develop remarkable resistance to radiation. Radioresistance represents a prominent obstacle in the effective treatment of cancer. Therefore, elucidation of the molecular mechanisms and pathways related to radioresistance in cancer cells is of paramount importance. In the present study, an integrative bioinformatics approach… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 114 publications
(74 reference statements)
1
13
0
Order By: Relevance
“…In many patients, cancer cells develop resistance to ionizing radiation (IR). Recently, an integrative bioinformatics analysis was applied to publicly available transcriptomic datasets of human cancer cells of different tissue origins treated with IR [ 87 ]. Supplemented with literature data, this analysis led to the identification of a panel of interconnected genes, belonging to pathways involved in neoplastic processes and implicated in the mechanisms of resistance to IR.…”
Section: Methodsmentioning
confidence: 99%
“…In many patients, cancer cells develop resistance to ionizing radiation (IR). Recently, an integrative bioinformatics analysis was applied to publicly available transcriptomic datasets of human cancer cells of different tissue origins treated with IR [ 87 ]. Supplemented with literature data, this analysis led to the identification of a panel of interconnected genes, belonging to pathways involved in neoplastic processes and implicated in the mechanisms of resistance to IR.…”
Section: Methodsmentioning
confidence: 99%
“…For microarray data analysis, the two-sample t-test was employed to identify genes differentially expressed in two groups: (i) leukemic blast cells from AML (n = 26) versus BM (n = 10), and (ii) AML (n = 26) versus PB (n = 10) (Table S1), by applying a methodology described in detail in previous studies [97,98]. The Benjamini-Hochberg method [85] for controlling FDR was applied; an FDR-adjusted p value less than or equal to 0.01 was considered as statistically significant in this study.…”
Section: Microarray-based Transcriptomic Data Analysismentioning
confidence: 99%
“…x FOR PEER REVIEW 4 of 14 In the generated network, the antiapoptotic BCL2 [39] is linked to hypertension, diabetes mellitus and colon cancer (Figure 2). Of note, studies have shown that BCL2 regulates radioresistance in colon cancer cells [40] and is up-regulated in radioresistant breast cancer cells [41]. Higher incidence of cardiovascular problems has also been observed in breast cancer patients when irradiated on the left breast versus the right, which is related to the late effect of RT [42].…”
Section: Retrieval Of Genesmentioning
confidence: 99%
“…The pro-apoptotic BAX (BCL2-associated X protein) [50], was found to be downregulated in acute lymphoblastic leukemia (ALL) and breast cancer cells resistant to radiation [41]. BAX is also linked to non-neoplastic diseases of different tissue origin (Figure 2), suggesting also a potential role of this molecule in radiotoxicity.…”
Section: Associations Among Genes Cancers and Non-neoplastic Diseasesmentioning
confidence: 99%
See 1 more Smart Citation